Functional Positioning and Realization Mechanisms of Digital Libraries in the Construction of the University Student Innovation and Entrepreneurship Support System - Nan Liu (Journal of Innovation and Entrepreneurship, 2025)
Against the backdrop of the national innovation-driven development strategy and the wave of mass entrepreneurship and innovation, universities have become the main front for cultivating innovative and entrepreneurial talents. As the knowledge and information hub of universities, digital libraries are transcending their traditional role as literature service providers and transforming into deep-service facilitators for innovation and entrepreneurship education. This paper aims to systematically explore the core functional positioning and realization mechanisms of digital libraries within the university student innovation and entrepreneurship support system. The research posits that the functions of digital libraries should be positioned as: a strategic aggregator of innovation and entrepreneurship resources; an Embedded Support for full-chain literacy education; a creator of virtual-physical integrated maker practice spaces; and a collaborative support platform for smart services. To realize these functions, it is necessary to construct a collaborative realization mechanism centered on “resources-technology-space-librarians,” which specifically includes: building a panoramic and intelligent digital resource system for innovation and entrepreneurship; creating immersive and personalized smart learning and practical training environments; providing professional, discipline-oriented Embedded Support; and establishing an open, collaborative, and sustainable ecological operation model. Combining case analysis, this study points out current challenges such as insufficient resource integration, room for improvement in service precision, a singular competency structure among librarians, and ineffective cross-boundary collaboration mechanisms. Corresponding optimization paths are proposed to provide theoretical reference and practical guidance for the deep integration of university libraries into innovation and entrepreneurship education and the construction of a high-quality support system.